Strategi Public Relations Dalam Promosi Sekolah Untuk Meningkatkan Intake Sma Kristen Satya Wacana Salatiga - Isna Caesar Cahyani; Lina Sinatra Wijaya (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study examines public relations (PR) strategies in school promotion and their role in increasing student intake at SMA Kristen Satya Wacana Salatiga. Using a qualitative descriptive approach, data were collected through in-depth interviews with the Promotion Division and school management, focus group discussions (FGDs) with Grade X students, and documentation of promotional activities. Data were analyzed thematically using the Attention, Interest, Desire, and Action (AIDA) framework. The findings show that PR strategies were effective at the early stages of communication, particularly in generating attention and interest through social media, face-to-face promotion, and interpersonal communication. At the desire stage, promotional activities contributed to building a positive school image and stimulating prospective students’ interest in further engagement. However, effectiveness at the action stage—enrollment decisions—remained limited, as indicated by a declining trend in student intake over the past three years despite consistent promotional efforts. This limitation is primarily due to the absence of structured, continuous follow-up communication, including a lack of a prospective student database and minimal post-promotion engagement. Consequently, initial interest and desire were not fully converted into enrollment actions, resulting in suboptimal student intake outcomes.